DNA Methylation Profiling Reveals the Change of Inflammation-Associated ZC3H12D in Leukoaraiosis - Huang, Wen-Qing; Yi, Ke-Hui; Li, Zhi; Wang, Han; Li, Ming-Li; Cai, Liang-Liang; Lin, Hui-Nuan; Lin, Qing; Tzeng, Chi-Meng (Frontiers in Aging Neuroscience, 2018)
Leukoaraiosis (LA) is neuroimaging abnormalities of the cerebral white matter in elderly people. However, the molecular mechanisms underlying the cerebral white matter lesions remain unclear. Here, we reported an epigenetic basis and potential pathogenesis for this complex illness. 317 differentially methylated genes were identified to distinguish the mechanism of occurrence and progression of LA. Gene-Ontology pathway analysis highlighted that those genes with epigenetic changes are mostly involved in four major signaling pathways including inflammation and immune response-associated processes (antigen processing and presentation, T cell costimulation and interferon-γ-mediated signaling pathway), synapse assembly, synaptic transmission and cell adhesion. Moreover, immune response seems to be specific to LA occurrence and subsequent disruption of nervous system functions could drive the progression of LA. The significant change of inflammation-associated ZC3H12D in promoter methylation and mRNA expression was implicated in the occurrence of LA, suggesting its potential functions in the molecular mechanism of LA. Our results suggested that inflammation-associated signaling pathways were involved in the pathogenesis of LA and ZC3H12D may contribute to such inflammatory process underlying LA, and further echoed it as a neuroinflammatory disorder in central nervous system (CNS).